SPROGLIG RELATIVISME: Hvordan og hvornår kommer den til udtryk i ontogenesen? - De Lopez, Kristine Jensen (Tidsskriftet Antropologi, 2006)
The paper is a theoretical and empirical contribution to the debate regarding the principle of language relativity in relation to ontogenesis. In the first part of the paper it is argued that the division between universal knowledge and culture-specific knowledge which is present in the new discipline of cognitive science is based on a false dichotomy. This has led to the ignorance of the complementary contributions that anthropology and developmental psychology may offer for the investigation of different human knowledge systems. The status quo regarding recent empirical evidence that demonstrates how language effects cognition is then presented and discussed in terms of ecological validity. The second part of the paper presents results from a recent cross-cultural and crosslinguistic study that demonstrates the early effect of language on cognition. The study investigates Danish (Scandinavian) and Zapotec (Mexican indigenous) infants’ spatial cognition with respect to whether this is influenced by the specific linguistic structure of each of the two languages. The results show that the two groups of children performed in different, language-specific ways to the presented spatial task. Danish children expressed a preference for imitating the behaviour of placing one object inside a another object, whereas the Zapotec children were equally apt to place the respective objects in an occlusive relationship. The results are discussed with regard to whether they give support to the Whorfian hypothesis or to the notion of cultural relativity, as reflected in the work of Vygotsky.